Analysis of the Amendments in IAS 7 and IFRS 7 within the Scope of Supplier Finance Arrangements - Seçil Sigali; Reha Memişoğlu (Muhasebe Enstitüsü Dergisi)
Supplier finance-reverse factoring transactions have positive effects on supply chain finance and resilience, mainly by lowering the financing costs of suppliers that are mostly small- and medium-sized enterprises. However, these transactions have become one of the focal points of the discussions on corporate governance and agency problems due to the lack of transparency in the disclosures and financial reporting issues, leading to the bankruptcies of Carillion and Greensill Capital, and the effects Greensill Capital’s bankruptcy had on the collapse of Credit Suisse in March 2023. On May 25, 2023, International Accounting Standards Board published mandatory disclosures on supplier finance arrangements that would be effective for annual reporting periods beginning on or after January 1, 2024 through its amendments to the International Accounting Standard 7 Statement of Cash Flows and International Financial Reporting Standard 7 Financial Tools. The aim of this study is to analyze these amendments by evaluating the reasons and targets of these changes, which credit rating agencies and auditors insistently request. The amendments are expected to positively impact how the effects of supplier financing are measured on buyer companies’ financial statements and to reduce the manipulative use of supplier finance arrangements by lowering information asymmetry and agency problems, thus increasing the positive effects these transactions have on world trade.